Los efectos de la posverdad en la democracia - Rubio Núñez, Rafael (Revista de Derecho Político, 2018)
Resumen: Política y verdad no van siempre de la mano. Tradicionalmente la diversidad de actores políticos, el derecho a la información y el papel de los medios de comunicación ha logrado un equilibrio imprescindible para el desarrollo de la democracia. La tecnología ha transformado de manera revolucionaria la comunicación, impactando en las formas de captar, almacenar, producir, distribuir y percibir la información convertida en materia prima imprescindible de las relaciones económicas, industriales y sociales. Esta transformación afecta de manera especial a la política, con la aparición de un nuevo tipo de trastornos informativos que inciden no sólo en la capacidad de distribución, sino también en el tiempo de la misma, la sentimentalización de las decisiones políticas, la fragmentación de la opinión pública, la creación de esferas públicas paralelas polarizadas y la creación de un clima de sospecha general que pone en cuestión el papel de la verdad y pone en peligro la democracia, más allá de los periodos electorales. Summary: 1. Communication and Society. 1.1. Truth and Politics: a weird relationship. 2. Not such a novelty. 3. What is post-truth politics? 3.1. What is new about post-truth politics? 3.1.a. Fiction or reality? 3.1.b The importance of image. 3.1.c A distorted reality. / The distortion of reality. 3.1.d. Timing. 3.1.e. Transparency and information overload. 3.1.f. Perception and cognitive dissonance. 3.1.g. Fragmentation and polarization. 3.1.h. Hyperconnectivity and communication parties. 4. Truth and Democracy. 5. The effects of post-truth politics on democracy. 6. Catalonia: a testing ground for post-truth politics. Abstract: Politics and truth do not always go hand in hand. Traditionally, the diversity of political actors, access to information and the role of the media have achieved an essential balance for the development of democracy. Technology has transformed communication in a revolutionary way, influencing the ways of producing, transmitting, distributing and perceiving information, converted into essential raw material for economic, industrial and social relations. This transformation affects politics in a special way, with the appearance of a new type of information disruptions which affect not only the distribution capacity, but also the timing of it, the sentimentalization of political decisions, the fragmentation of the public opinion, the creation of polarized parallel public spheres and the creation of a climate of general suspicion that questions the role of truth and endangers democracy, beyond the electoral periods.